Erratum: Intensitas VO2max Melalui Interval Training dan Circuit Training - Firmansyah Dahlan; Alimuddin Alimuddin (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.581 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.